The Structural Design and Analysis of the Multi Nozzle Relay Air-Jet Inserting System by Profile Reed Guiding for 3D Weaving Machine - Wang, Yixuan (Recent Patents on Mechanical Engineering, 2026)
IntroductionBased on the author’s invention patent literature, this article designs a parameterized simulation model of a multi-layer jet weft insertion system by profiles reed guidance for a 3D loom on the PTC Creo9.0 platform, including the main supersonic nozzle, supersonic auxiliary nozzle (relay nozzle), and multi-slot profiles reed components.MethodsBased on the existing basic theory, experimental results, and empirical data of turbulent jet, the parameters of the multi-layer jet weft insertion system, as well as the structural parameters and the relative positions of the main, auxiliary nozzle and profile reed components, such as the center distance of each layer's main nozzle, auxiliary nozzle spacing, auxiliary nozzle installation angle, spray direction angle, and spray angle, have been determined preliminarily.ResultsFurther, the basic flow field parameters, such as the supply pressure of the main and auxiliary nozzles and the shape of multi-layer profile reeds, have been determined optimally on the Virtual Prototype Collaborative Simulation Platform (PTC Creo9.0/ANSYS Workbench/Fluent 2024R1), and the rationality of the structural design also been verified; on the premise of ensuring that the airflow velocity of each layer's profiles groove meets the requirements of weft insertion, the design and simulation calculation is repeatedly modified, and the optimal structural design parameters of the multi-layer weft insertion system and nozzle is finally determined.ConclusionTo explore the feasibility of multi-layer jet weft insertion, the design of three-dimensional multi-layer jet weft insertion looms has laid a theoretical foundation, laying a good foundation for the emergence and industrial manufacturing of three-dimensional multi-layer jet weft insertion looms, and providing an important reference for the innovative design of three-dimensional multi-layer water jet weft insertion looms.
Keywords: intersecting jet